COMMUNICATION-BASED ENVIRONMENTAL LITERACY STRATEGY TO ADDRESS POLLUTION IN SANGIR BATANGHARI - Yulita, Yulita; Sulastri, Irta; Hermawati, Hermawati (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
This research has the objective of how environmental literacy-based communication strategies to overcome pollution in Sangir Batanghari. In this framework, environmental literacy-based communication development strategies become crucial to provide knowledge about environmental protection and increase participation and active involvement of the community in sustainable development. In this research, a qualitative method was used by using in-depth interviews, participatory observation, and document analysis as data collection techniques. The findings of this research show that Local Community Involvement is inviting local communities in development planning and decision-making as well as collaborating with non-governmental organizations. The results of this research provide an important contribution to the understanding of environmental pollution in providing knowledge and communication strategies for sustainable development in supporting empowerment in the Subdistrict of Sangir Batanghari. Communication strategy as an effort to overcome environmental pollution with several stages, namely, the assessment stage, the planning stage, the message production stage, and the reflection stage.